2023
DOI: 10.1111/1744-7941.12376
|View full text |Cite
|
Sign up to set email alerts
|

How does supervisor developmental feedback make employees sense the meaning of work?

Abstract: This article used 677 questionnaires obtained by stratified sampling as a sample and used the hierarchical regression analysis method and the bootstrap method to analyze the data. Based on Self‐Determination Theory, this article integrated the Leader‐Member Exchange (LMX) situation to explore the mechanism of supervisor developmental feedback on employees' work meaningfulness. The results showed that supervisor developmental feedback aroused employees' work meaningfulness by meeting the autonomy need and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…However, while these studies have contributed to enriching relevant theories, few scholars have focused on the boundary role of leadership feedback in this context. Studies by Cai et al, 28 Zhang et al, 30 and Li et al 46 have shown that supervisor developmental feedback, as a positive form of feedback, can effectively regulate employees’ psychological states, ignite their intrinsic interest in tasks, and help them experience the positive meaning of work. Therefore, we introduce supervisor developmental feedback as a moderating variable and explore its moderating role in the double pathways, finding that supervisor developmental feedback can both mitigate the negative impact of illegitimate tasks on work withdrawal and enhance the positive impact of illegitimate tasks on job crafting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, while these studies have contributed to enriching relevant theories, few scholars have focused on the boundary role of leadership feedback in this context. Studies by Cai et al, 28 Zhang et al, 30 and Li et al 46 have shown that supervisor developmental feedback, as a positive form of feedback, can effectively regulate employees’ psychological states, ignite their intrinsic interest in tasks, and help them experience the positive meaning of work. Therefore, we introduce supervisor developmental feedback as a moderating variable and explore its moderating role in the double pathways, finding that supervisor developmental feedback can both mitigate the negative impact of illegitimate tasks on work withdrawal and enhance the positive impact of illegitimate tasks on job crafting.…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has shown that supervisor developmental feedback, as a guiding and supportive information feedback, can provide employees with sufficient work resources, enhance their self-efficacy and work passion, improve their work performance, and promote their innovative behaviors. 28,30,46 Therefore, we suggest that supervisor developmental feedback is likely to influence individual psychological, cognitive, or behavioral responses in conflict situations, and high levels of supervisor developmental feedback are likely to weaken employees' interpretation of the threat posed by illegitimate tasks.…”
Section: The Moderating Role Of Supervisor Developmental Feedbackmentioning
confidence: 95%
See 3 more Smart Citations